2000
DOI: 10.1520/jfs14749j
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints and DNA: STR Typing of DNA Extracted from Adhesive Tape after Processing for Fingerprints

Abstract: An exhibit that is often received for examination in cases of robbery or terrorist activity is adhesive tape. This type of exhibit can often, but not always, be successfully processed for fingerprints. The question arises whether or not it is possible to extract and type DNA after the tape has been sequentially processed for fingerprints. In this work, various donors left fingerprints on the adhesive side of tapes. The tapes were then sequentially processed for fingerprints using an alternate light source, cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 2 publications
0
25
0
1
Order By: Relevance
“…No interference, but may depend on thickness of deposition and DNA extraction method Stein et al 1996;Zamir et al 2000b;von Wurmb et al 2001;Grubwieser et al 2003;Bille et al 2009 Chemical methods…”
Section: Evidence Collection and Preservation At The Crime Scene And mentioning
confidence: 99%
“…No interference, but may depend on thickness of deposition and DNA extraction method Stein et al 1996;Zamir et al 2000b;von Wurmb et al 2001;Grubwieser et al 2003;Bille et al 2009 Chemical methods…”
Section: Evidence Collection and Preservation At The Crime Scene And mentioning
confidence: 99%
“…It has previously been reported that fingerprinting techniques (including those using powder) do not hinder the obtaining of DNA profiles from treated samples (6,(11)(12)(13)(14)(15). If, however, fingerprinting powder were to remain in the DNA sample after extraction (as has on occasion been noted when performing Chelex extractions followed by using Centricons R and/or Microcons R to concentrate the sample) and inadvertently added to the PCR mix, would it inhibit the amplification?…”
Section: Experiments 3: Inhibitionmentioning
confidence: 99%
“…The standard procedure for fiber investigations was, and still is, to tape corpses, items of clothing or any other items of evidential value with a special kind of adhesive tape and to microscopically and painstakingly search these tapings step-by-step noting the position of any fibers suspected of having been transferred from one item to the other [1]. Fiber investigations nowadays play a subordinate role to DNA in forensic investigations, although they have not been completely discarded and can sometimes be of vital importance.…”
Section: Introductionmentioning
confidence: 99%